Pemetaan Stimulasi Pengembangan Aspek Agama Dan Moral Pada Masa Pandemi - La Hewi; Suni Sundari (PAUDIA : Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2023)
AbstractDevelopmental stimulation of children becomes the task and responsibility of educators. Developmental stimulation in the aspects of religion and morality is one of the developments that must be stimulated. This research aims to analyze the actualization of stimulation of the religious and moral aspects of children, and how to overcome obstacles encountered during online learning in early childhood education institutions in Kendari city. The researcher used a qualitative approach with a phenomenological method to gain in-depth understanding. Interviews and documentation were used as data collection methods. The collected data were then analyzed using an interactive model, where the data analysis stages were data reduction, data presentation, inference, and verification. The results of the study showed that, first, the implementation of stimulation for the religious and moral aspects of children during the pandemic in Kendari city's early childhood education institutions used a combination of online and offline methods (online using WhatsApp group application; offline or face-to-face meetings in school conducted 2 to 3 times a week. The stimulation content was carried out by habituating religious teachings practices such as reading prayers before studying, memorizing daily prayers, and short surahs). Second, obstacles to the stimulation of religious and moral development were overcome by meetings with parents (home visits) to discuss their children's development during the implementation of learning at home.Keywords: religious and moral value; offline and; online AbstrakStimulasi perkembangan anak menjadi tugas dan tanggung jawab pendidik. Stimulasi perkembangan pada aspek agama dan moral merupakan salah satu perkembangan yang harus distimulasi. Penelitian ini bertujuan untuk menganalisis aktualisasi stimulasi aspek agama dan moral anak dan cara mengatasi hambatan yang didapatkan pada pelaksanaan pembelajaran daring di lembaga pendidikan anak usia dini di kota Kendari. Peneliti menggunakan pendekatan kualitatif dengan metode fenomenologi untuk mendapatkan pemahaman yang mendalam. Wawancara dan dokumentasi digunakan sebagai metode pengumpulan data. Data yang terkumpul kemudian dianalisis dengan menggunakan model interaktif, dimana tahapan analisis data adalah reduksi data, penyajian data, inferensi dan verifikasi. Hasil penelitian menunjukkan bahwa pertama, pelaksanaan stimulasi untuk aspek agama dan moral anak masa pandemi di lembaga PAUD kota Kendari menggunakan kombinasi daring dan luring (daring menggunakan aplikasi grup whatsApp; luring atau tatap muka di sekolah dilakukan 2 sampai 3 kali dalam seminggu. adapun konten stimulasi dilakukan dengan melakukan pembiasaan praktek ajaran agama seperti membaca doa sebelum belajar, menghafal doa-doa harian dan juga surah-surah pendek); kedua, hambatan stimulasi pengembangan agama dan moral diatasi dengan cara pertemuan dengan orang tua siswa (home visit) untuk membahas perkembangan anak selama pelaksanaan pembelajaran di rumah.Kata kunci: nilai agama dan moral; luring dan; daring